GASTRO INTESTINAL PARASITISM IN LARGE RUMINANTS OF KHAMMAM DISTRICT, TELAGANA STATE - Chandravati, T; Kumar, B Kiran (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Total 3250 fecal samples from buffaloes and cattle of different villages in Khammam district of Telangana state were screened during April-2010 to March 2013 to evaluate gastrointestinal parasitic load. Out of 3250 screened, 1905(58.52%) were positive for gastrointestinal parasites comprising (1052) 32.37% of Buffaloes and (853) 26.25% of cattle. Among these positives the incidence of nematodes, trematodes, protozoa and mixed infections in buffaloes was 53.43%, 31.27%, 9.03%, 6.27 % respectively whereas in cattle the incidence was observed to be 46.43%, 36.46%, 10.67%, 6.44 % respectively indicating higher incidence of nematode infections in both buffaloes and cattle. The incidence with Strongyloid and Amphistome were independent of season, whereas seasonal incidence of all the parasitic infections were to be higher in rainy season. The estimation of EPG count for strongyloides sps of cattle range from 200-4000, buffaloes range from 200-2000.The faecal egg counts of flukes ranged from 50-400 in cattle and 50-600 in buffaloes.
Keywords: Parasites; Cattle; Buffalo; faecal sample; incidence; Telangana